Working Capital and Financial Performance in the Energy Sector of Saudi Arabia: Moderating Role of Leverage - Shaik, Abdul Rahman; Ali, Anis; Alanazi, Ibtisam Dhuwayhi (International Journal of Energy Economics and Policy, 2023)
The current study examines the effect of working capital (measured in terms of current ratio) on firm performance in the listed firms of Saudi Arabian energy sector during the period starting from 2012 to 2019. A pooled and panel data model was used to analyze the extracted data. The findings indicate that working capital has a considerable beneficial impact on company performance and that leverage has a significant negative impact. Even after moderating by an interaction variable, working capital still has a substantial negative influence on corporate performance.